Unveiling and challenging the identity, formation, and evolution of Transformation Theory - Koulaouzidis, George Archimedes; Eschenbacher, Saskia; Romano, Alessandra; Soeiro, Dina (Adult Education Critical Issues, 2024)
In this contribution, we explore established and emerging facets that contribute to shaping the theoretical landscape of transformation theory. Throughout our discussion, we contemplate the multifaceted nature of transformative learning, acknowledging its positive evolution with diverse perspectives that have enriched the field. Despite this progress, we argue that challenges persist, prompting the recognition of transformative learning theory as an ongoing, dynamic paradigm capable of organically responding to the contemporary challenges of adult learning and education. Our discourse advocates for a deeper exploration of the theory’s potential for profound change, emphasizing the imperative to move beyond its dominant cognitive dimension.